Effect of Initial Scratch on Ship Bottom Plate Corrosion Rate and Structural Crashworthiness in Grounding Incidents - MURSID, Ocid; ALFARIS, Dean Nadhif; TUSWAN, Tuswan; ZAKKI, Ahmad Fauzan; WINDYANDARI, Aulia; MALAU, Karno R.; NUBLI, Haris (Engineering Transactions, 2025)
Hitting an object in the ocean can peel off the coating on a ship’s plate. The exposed plate can be vulnerable to corrosion because it is exposed to the environment and seawater, which can degrade its strength. So, the crashworthiness of the bottom plate should be evaluated in the event of a grounding incident. The ratio of the scratch area and the number of stripes are used as experimental variables. Based on seawater corrosion experiments, the plate’s corrosion rate increases quadratically with the scratch area, which is then used for grounding simulations. Eighteen grounding scenarios, based on scratch size, dimensions, and corrosion exposure, reveal that only two or three stripes significantly reduce the plate’s strength in simulations. In addition, in the case of two or three stripes of scratches, corrosion further reduces the plate’s strength in the grounding simulations. This plate has limited space in the vertical direction, which influences the horizontal stripe of scratches and affects the plate’s strength in grounding simulation, as compared to the vertical stripes. Besides this, the pattern of crack propagation depends on the reaction force.